1986
DOI: 10.1111/j.1467-8624.1986.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Infant Temperament, and Parenting Self-Efficacy: A Mediational Model of Postpartum Depression

Abstract: A model of maternal postpartum depression was tested in which difficult infant temperament was construed as a stressor and supportive interpersonal relationships were construed as a protective resource. It was hypothesized that both infant temperamental difficulty and level of social support would affect maternal depression through the cognitive mediation of perceived self-efficacy in the parenting role. Participants were 55 married women who were assessed during pregnancy and again 3 months postpartum. Infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
78
1
12

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(105 citation statements)
references
References 43 publications
14
78
1
12
Order By: Relevance
“…Thus, social support influences depressive symptoms only to the extent that it has an impact on motivational processes. The present findings are consistent with previous research (Benight and Bandura 2004;Bisconti and Bergeman 1999;Cutrona and Troutman 1986;Saltzman and Holahan 2002;Smith et al 2000) and with the assumption that social support operates through adaptive mechanisms such as self-efficacy (Berkman et al 2000) and coping (Holahan et al 1997a).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, social support influences depressive symptoms only to the extent that it has an impact on motivational processes. The present findings are consistent with previous research (Benight and Bandura 2004;Bisconti and Bergeman 1999;Cutrona and Troutman 1986;Saltzman and Holahan 2002;Smith et al 2000) and with the assumption that social support operates through adaptive mechanisms such as self-efficacy (Berkman et al 2000) and coping (Holahan et al 1997a).…”
Section: Discussionsupporting
confidence: 93%
“…In a variety of studies, self-efficacy has been found to mediate the relationship between social support and depression (Benight and Bandura 2004;Cutrona and Troutman 1986;Saltzman and Holahan 2002). Other studies found personal resources such as self-esteem (Brown et al 1986), coping strategies (Holahan et al 1997b), and mastery (Jang et al 2002) played a role in the association between social support and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Three correlates of PPD are consistently found by researchers: marriage problems and lack of social support, particularly the father's (Table 1), infant problems, including pregnancy and delivery problems (Table 2), and a prior history of depression or other emotional problems (Atkinson and Rickel 1984;Cutrona and Troutman 1986;Gotlib et al 1991;Graff et al 1991;Logsdon et al 1994;O'Hara et al 1983O'Hara et al , 1984Whiffen 1988;Whiffen and Gotlib, 1993). This paper will propose three related adaptive functions for PPD that are consistent with the expectations of evolutionary theorists and the first two correlates noted above.…”
supporting
confidence: 63%
“…Most studies find a strong correlation between either a previous history of emotional problems, depression, or depression during pregnancy, and PPD (Atkinson and Rickel 1984;Cutrona and Troutman 1986;Gotlib et al 1991;Graff et al 1991;Logsdon et al 1994;O'Hara et al 1983O'Hara et al , 1984Whiffen 1988;Whiffen and Gotlib 1993). Unfortunately, the defection hypothesis does not clearly illuminate this important aspect of PPD.…”
Section: Tests Of the Defection Hypothesis For Postpartum Depressionmentioning
confidence: 99%
“…Although all parents 1 benefit from appropriate social support, it is more critical for parents of NNU babies-for whom a lack of social support is a predictor of distress-than for parents of full-term infants who are in good health (Singer, Davillier, Bruening, Hawkins, & Yamashita, 1996). Members of the social network act as a vital resource in helping these parents to meet the stressful demands placed upon them (Crnic, Greenberg, Ragozin, Robinson, & Basham, 1983;Cutrona & Troutman, 1986;McHaffie, 1992), but parents can find it difficult to identify who can help them and to ask for the help that they need (Logsdon & Davis, 1998). For their part, social network members want information about the baby's health state, how the parents are coping and what support the parents need, so that they can offer appropriate assistance (Moncur, Masthoff, & Reiter, 2008).…”
Section: Research Context: the Neonatal Unitmentioning
confidence: 99%